PENDAMPINGAN KOMITE SEKOLAH DALAM MENYUSUN PROGRAM KERJA - Istikomah Istikomah; Taufiq Churrahman; Mohamad Rojii; Nanik Midarnengsih; Elok Sundus (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The school committee is one of the independent institutions that has a role to improve the quality of education. However, the work program of committees at schools is not optimal yet. Like those are in SDN Bohar and SDN Suko. This is due to the lack of socialization regarding the Law on committees and the programs that must be drafted. Therefore, there is a need for socialization and assistance for committee members. The purpose of this dedication is to give knowledge and understanding of the importance of committee in the education unit. The target of this dedication is the caretaker of the school committee in SDN Bohar and SDN Suko with total of 22 people. The method is done in three steps. First, the preparation is done by a field survey by looking at the condition of the school and its committee members. The second stage held a meeting with committee members to explore the roles and tasks of the group. The third stage is in the form of assistance to develop work programs. The target for achievements are the committee caretaker understand their role in the education unit and be able to arrange work programs with the school principal to improve school quality. The result achieved was an increase in the committee's understanding of the Ministry of Education Regulation No.75 of 2016 concerning the school committee and the ability to arrange work programs